Baseline patterns of structural and functional diversity of benthic amphipods in the western Arabian Gulf. (March 2021) - Manokaran, Seerangan; Joydas, Thadickal V.; Qurban, Mohammad A.; Cheruvathur, Linoy L.; Kariyathil, Thomas J.; Basali, Abdullajid U.; Khan, Syed Ajmal; Al-Suwailem, Abdulaziz
Abstract: This work presents the structural and functional traits of benthic amphipods in the Saudi waters of the Arabian Gulf. Sixty-two species belonging to 37 genera and 17 families were recorded. Sensitive species such as Grandidierella bonnieroides, G . exilis, Gammaropsis atlantica and Caprellidea indet., were mostly dominant. The average values of richness, density and diversity (H′ log2 ) were 11 ± 1, 512 ± 232 ind. m-2 and 3.1 ± 0.1 respectively. The density decreased with increased in depth (nearshore (NS) - 784 ± 445 and offshore (OS) - 222 ± 28, p  = 0.023), while evenness (NS – 0.93 and OS -0.94) and diversity (NS – 3.10 and OS - 3.18) were unaffected by depth. Interstitial space dwellers (56.76%) and surface deposit feeders (60.16%) were dominant in the nearshore sand substratum. However, domicolous (72.2%) with suspension and surface deposit feeders (71.7%) were more in offshore silt sediments. The combination of depth, pH and TPH ( p  = 0.249) influenced the distribution of amphipods. Highlights: A baseline study on of benthic amphipods from the western Gulf was made for the first time. A comparable number of species with the other parts of the Indian Ocean was recorded. Deposit and suspension feeders were the most dominant functional groups. Distinct functional patterns of amphipods in sand and silt habitats were observed. The distribution of amphipods were influenced by depth, pH and TPH.